The Republic of Men : Gender and the Political Parties in Interwar France - Read, Geoff, 1975- (Book collections on Project MUSE., 2014)
In The Republic of Men, Geoff Read explores the intersection of gender bias and the eight most important political parties in interwar France, breaking new scholarly ground in profound ways. The first to compare gender discourse across the political spectrum in a national context and trace the origins of the fascist ""new man"" in other political traditions, Read evaluates the impact of gender discourse upon policy during a pivotal period in French history. Skillfully exploring how differing political traditions -- from left to right -- influenced and reacted to each other, Read shows